2014
DOI: 10.1017/s1460396914000107
|View full text |Cite
|
Sign up to set email alerts
|

Trimodality bladder-sparing approach versus radical cystectomy for invasive bladder cancer

Abstract: Purpose: To compare the outcome among patients with invasive bladder cancer treated with cystectomy alone with outcome among those treated with combined-modality treatment in a randomised phase III trial.Patients and methods: Patients with histologically confirmed invasive non-metastatic bladder cancer T2-3, N0 and M0 were randomly assigned to two arms: Arm 1: of which all patients underwent radical cystectomy (RC) alone; and Arm 2, of which all patients were subjected to maximal transurethral resection of bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The 3-year OS for the trimodality group and the RC group were 61 & 63%, respectively (p = 0·425), while the DSS were 69 & 73%, respectively (p = 0·714). The 3-year OS with intact bladder was 50% [28].…”
Section: Discussionmentioning
confidence: 96%
“…The 3-year OS for the trimodality group and the RC group were 61 & 63%, respectively (p = 0·425), while the DSS were 69 & 73%, respectively (p = 0·714). The 3-year OS with intact bladder was 50% [28].…”
Section: Discussionmentioning
confidence: 96%
“…In this single-institution pilot feasibility trial, we noticed that the proportion of patients with a diagnosis of MIBC in whom cystectomy and radiation therapy were both valid options was not as high as reported in the previous retrospective CMT series. [7,16,17,[21][22][23] This may reflect certain degree of selection bias. For example, Kulkarni et al [16] observed no difference between RC and CMT in regard to OS (35.7% vs 39.3%; p=0.63) in a single institutional series.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 1915 studies were excluded for wrong population, topic, study design, outcome, publication type, intervention or lack of comparison group, and 6 studies were included in the final analysis (Fig. 1) (Algizawy et al, 2014;Huddart et al, 2017;Kim et al, 2017;Kulkarni et al, 2017;Gofrit et al, 2015;Boustani et al, 2018). The randomized non-inferiority study published by Algizawy et al in 2014 compared patients with T2-T3, N0 stage non-metastatic MIBC undergoing TMT or RC.…”
Section: Overall Survival Disease Specific Survival Complete Patholog...mentioning
confidence: 99%
“…However, the results of this study were limited by very serious imprecision bias regarding OS and CSS, due to the inadequate sample size. Furthermore, a significant risk of performance and detection bias was assessed for the outcomes of pCR and CSS, in consideration of the open design of the study (Algizawy et al, 2014). Huddart et al published in 2017 a non-inferiority randomized trial comparing TMT and RC, enrolling 45 patients with performance status 0 and stage T2-T3 N0 M0 transitional bladder cancer.…”
Section: Overall Survival Disease Specific Survival Complete Patholog...mentioning
confidence: 99%